How should business travel time savings be valued?. Issue 4 (December 2015) - Wardman, Mark; Batley, Richard; Laird, James; Mackie, Peter; Bates, John
Abstract: This paper provides the most extensive appraisal yet of the methods for valuing business travel time savings. From both theoretical and empirical perspectives, we review the traditional Cost Savings Approach (CSA), which has long been dominant in appraisal practice worldwide, alongside its main rivals, namely the Hensher Equation (HE) and the Willingness-To-Pay (WTP) approach. We conclude that the CSA does not provide a suitable basis for valuing business travel time savings. The HE and WTP approach do not tell the same story in terms of absolute values or variations in values according to key factors, but it is not clear which is the more appropriate. Further detailed exploratory research is needed into how employers value the benefits of employees' time savings. We recommend a carefully controlled triangulation of the CSA, HE, employers' WTP and employees' WTP, not seen since the pioneering work of Fowkes, Marks and Nash in 1986. Highlights: Extensive review of valuation of time savings for briefcase business travellers. Compares Cost Savings Approach, Hensher Equation and Willingness-to-Pay. Cost Savings Approach not suitable for valuing business travel time savings. Hensher Equation and Willingness-to-Pay give different values and variations in them. Research into how companies decide and triangulation of different methods needed.